p²-q²
Б) (p-q) (p+q)
x1 = -re(acos(-3)) + 2*pi - i*im(acos(-3))
x2 = 2*pi - i*im(acos(4))
x3 = re(acos(-3)) + i*im(acos(-3))
x4 = re(acos(4)) + i*im(acos(4))
Объяснение:
x1 = -re(acos(-3)) + 2*pi - i*im(acos(-3))
x2 = 2*pi - i*im(acos(4))
x3 = re(acos(-3)) + i*im(acos(-3))
x4 = re(acos(4)) + i*im(acos(4))
x1 = 3.14159265358979 + 1.76274717403909*i
x2 = 6.28318530717959 - 2.06343706889556*i
x3 = 3.14159265358979 - 1.76274717403909*i
x4 = 2.06343706889556*i
сумма
-re(acos(-3)) + 2*pi - i*im(acos(-3)) + 2*pi - i*im(acos(4)) + i*im(acos(-3)) + re(acos(-3)) + i*im(acos(4)) + re(acos(4))
=
4*pi + re(acos(4))
произведение
(((-re(acos(-3)) + 2*pi - i*im(acos(-3)))*(2*pi - i*im(acos(4*(i*im(acos(-3)) + re(acos(-3*(i*im(acos(4)) + re(acos(4)))
=
-(2*pi - i*im(acos(4)))*(i*im(acos(-3)) + re(acos(-3)))*(i*im(acos(4)) + re(acos(4)))*(-2*pi + i*im(acos(-3)) + re(acos(-3)))
x-4x^2 \ x - 1 > 0
1) x - 1 не равен 0 > x не равен 1
2) x - 4x^2 > 0
x*(1 - 4x) > 0
x > 0
1 - 4x > 0
- 4x > - 1
4x < 1
x < 0.25
>
0 0.25 1
ответ от нуля до 0.25 (указанные числа не входят)
Б
Объяснение:
Формула різниці квадратів